Hubungan Antara Hipertensi dengan Stroke Berulang di RS Al-Islam Bandung - Farras Nur Muhamad; Ratna Dewi Indi Astuti; Ismawati (Bandung Conference Series: Medical Science, 2024)
Abstract. Recurrent stroke is a condition where an individual experiences multiple stroke attacks after having previously suffered a stroke. Uncontrolled risk factors can be significant triggers for recurrent stroke, including hypertension. This study aims to explore the relationship between hypertension and recurrent stroke, whether ischemic or hemorrhagic stroke. The research methodology employed is an analytical observational study with a case-control approach. A total of 180 respondents participated in this study, comprising 30 cases of recurrent ischemic stroke, 30 cases of recurrent hemorrhagic stroke as the case group, and 60 patients each of non-recurrent ischemic and hemorrhagic stroke as the control group. Sampling was conducted using non-probability sampling techniques, employing quota sampling for the case group and stratified random sampling for the control group. Data collection involved the observation of medical records to obtain a history of hypertension and recurrent stroke events. Data analysis was performed using chi-square tests and odds ratios to assess the level of hypertension risk associated with recurrent stroke events. The research findings indicate a significant relationship between hypertension and recurrent ischemic stroke (ρ value < α, ρ = 0.002842, OR = 4.03), while no significant association was found between hypertension and recurrent hemorrhagic stroke (ρ value > α, ρ = 0.05239, OR = 2.444). In conclusion, this study confirms the significant role of hypertension in increasing the risk of recurrent ischemic stroke. However, there is no significant relationship between hypertension and recurrent hemorrhagic stroke. Abstrak. Stroke berulang merupakan kondisi di mana seseorang mengalami serangan stroke lebih dari sekali setelah sebelumnya telah mengalami stroke. Faktor-faktor risiko yang tidak terkontrol dapat menjadi pemicu utama terjadinya stroke berulang, di antaranya adalah hipertensi. Penelitian ini bertujuan untuk mengeksplorasi hubungan antara hipertensi dan kejadian stroke berulang, baik itu stroke iskemik maupun perdarahan. Metode penelitian yang digunakan adalah penelitian observasional analitik dengan pendekatan case-control. Sebanyak 180 responden terlibat dalam penelitian ini, dengan 30 pasien stroke iskemik berulang, 30 pasien stroke perdarahan berulang sebagai kelompok kasus, dan 60 pasien stroke iskemik serta 60 pasien stroke perdarahan yang tidak mengalami kejadian berulang sebagai kelompok kontrol. Pengambilan sampel menggunakan teknik non-probability sampling dengan quota sampling untuk kelompok kasus dan stratified random sampling untuk kelompok kontrol. Data dikumpulkan melalui observasi rekam medis untuk mendapatkan riwayat hipertensi dan kejadian stroke berulang. Analisis data dilakukan menggunakan uji chi-square dan odds ratio untuk menilai tingkat risiko hipertensi terhadap kejadian stroke berulang. Hasil penelitian menunjukkan adanya hubungan antara hipertensi dan kejadian stroke iskemik berulang (ρ value < α, ρ = 0,002842, OR = 4,03), namun tidak terdapat hubungan yang signifikan antara hipertensi dan kejadian stroke perdarahan berulang (ρ value > α, ρ = 0,05239, OR = 2,444). Kesimpulannya, penelitian ini menegaskan bahwa hipertensi berperan penting dalam meningkatkan risiko kejadian stroke iskemik berulang. Meskipun demikian, tidak terdapat hubungan yang signifikan antara hipertensi dan kejadian stroke perdarahan berulang.